Diseño y simulación de un banco de pruebas aerodinámico (túnel de viento) para la validación de simulaciones con software CFD - Bustillos Hidalgo, Boris Alfonso (2018)
The present research project is directed to the study of fluid mechanics. The main objective is the design and simulation of the operation of an aerodynamic test bench or wind tunnel for the validation of simulations of vehicle profiles in velocity and pressure of contour flow paths using Computational Fluid Dynamics software or by its acronym CFD. This tunnel will allow to verify the effects of wind current that occur, to demonstrate the efficiency and aerodynamic specification of bodies to scale, test yields within the simulation, highlighting these of a wide variety of studies that can be developed; all justified with its corresponding cost analysis as a consideration that the project will be manufactured to benefit the career. It is important to highlight knowledge in Aerodynamics, Mechanical Design and simulations in CFD software, establishing that a wind tunnel is a specially designed and protected instrument, in which the ambient air is extracted or pushed, by mechanical means in order to reach a specific speed and a predetermined flow pattern at a parameterized time. All this action can be monitored from the outside through the testing section. The flow characteristics can be measured using specialized instruments. The research project consists of seven chapters in which different topics are studied, justified and explored according to the importance considered. The following chapters are presented, delimiting the bases of the project: In chapter I, the contextualization of the research, the problem and its derivatives, the proposed objectives, the justification, the variables and limitations of it are manifested. The methodological aspects that it infers are analyzed. Chapter II considers the theoretical foundation of the research, that is, the theoretical framework related to the aerodynamic test bench, its characteristics and components. Some aspects are known such as Aerodynamics, the phases and interactions in the design process, the principles of its operation based on the classification of the flow in the process according to the number of Mach, likewise will be properly exposed the support of the equations that will be exposed in the results. In chapter III, the corresponding research methodologies are presented, referring to the types of research, methods and design of the presented research. The required instruments for research and human resources are exposed following a control and detail of data. In chapter IV, the results are supported by the discussion and interpretation of the data discovered in the process of research development. Chapter V presents the conclusions of the investigation and the recommendations that can be applied. Chapter VI justifies the textualization of the theoretical basis of the research through its corresponding bibliography, stating its title, author and year of publication. Chapter VII culminates with the annexes to the research project, tables and catalogs that were necessary for its development. Keywords: Computational Fluid Dynamics, Aerodynamics, software